Effect of parental knowledge and attitude in the control of childhood asthma - Venugopal, Sreeram; Namboodiripad, Aparna (International Journal of Contemporary Pediatrics, 2016)
Background:Asthma is responsible for 250,000 deaths and 1% of all the DALY (disability-adjusted life year) worldwide. It is a leading cause of school absenteeism among children and incurs a large financial burden. Parents of children with asthma have varied beliefs and knowledge about asthma and its treatment which may affect the control of asthma. Methods: A cross-sectional study was carried out among parents of children who attended the asthma clinic of a tertiary care centre in central Kerala, India using a questionnaire. Results:A total of 303 parents were enrolled in the study. The mean age of the asthmatic children was 5.36±1.8 years with a male to female ratio of 1.16:1. In the study group 48.18% (146/303) of the parents correctly answered >60% (at least 7 correct answers out of 11) of the knowledge questions (mean = 6.57±2.06) while only 17.16% (52/303) of the parents correctly answered >60% (at least 4 correct answers out of 7) of the attitude questions (mean = 3.20±1.33). A statistically significant association (P = 0.0035) was found between knowledge levels (<or> 60% of the knowledge questions correctly answered) and control of asthma. And a similar association (P = 0.0135) was also seen between attitude levels (<or> 60% of the attitude questions correctly answered) and control of asthma. Conclusions:Even though parents had better knowledge of asthma than attitude, the control of asthma was related to the level of both knowledge and attitude of parents. Keywords: